DECUSSATE network with flowering genes explains the variable effects of qDTY12.1 to rice yield under drought across genetic backgrounds - Sanchez, Jacobo; Kaur, Pushpinder Pal; Pabuayon, Isaiah C. M.; Karampudi, Naga Bhushana Rao; Kitazumi, Ai; Sandhu, Nitika; Catolos, Margaret; Kumar, Arvind; de los Reyes, Benildo G. (Wiley, 2022)
The impact ofqDTY12.1in maintaining yield under drought has not been consistent across genetic backgrounds. We hypothesized that synergism or antagonism with additive‐effect peripheral genes across the background genome either enhances or undermines its full potential. By modeling the transcriptional networks across siblingqDTY12.1‐introgression lines with contrasting yield under drought (LPB = low‐yield penalty; HPB = high‐yield penalty), theqDTY12.1‐encodedDECUSSATEgene (OsDEC) was revealed as the core of a synergy with other genes in the genetic background.OsDECis expressed in flag leaves and induced by progressive drought at booting stage in LPB but not in HPB. The uniqueOsDECsignature in LPB is coordinated with 35 upstream and downstream peripheral genes involved in floral development through the cytokinin signaling pathway. Results support the differential network rewiring effects through genetic coupling–uncoupling betweenqDTY12.1and other upstream and downstream peripheral genes across the distinct genetic backgrounds of LPB and HPB. The functionalDEC‐network in LPB defines a mechanism for early flowering as a means for avoiding the drought‐induced depletion of photosynthate needed for reproductive growth. Its impact is likely through the timely establishment of stronger source‐sink dynamics that sustains a robust reproductive transition under drought.